Buruh vs Perusahaan (Studi Kasus Konflik Buruh/ Pekerja Driver Go-Jek dengan PT Go-Jek Indonesia) - Randi Randi; Sonia Nurprameswari; Nita Apriliani (Jurnal Empirika, 2017)
The development of trade unions in Indonesia very rapidly. The development course of the growth of big companies in Indonesia. With the development of the number of workers increasing and labor rights is increasingly noteworthy either by the Government, the company and the workers ' organization itself. As for the focus in this paper, will discuss how the labour conflict drivers and PT gojek Go-Jek-based technology, and safety valves in the conflict. The reason for maintaining the social structure in the company needed a "win win solution". As Coser explained that conflicts can maintain or establish new social strutur, and safety valve acts as a reducer of the conflict between the two parties, a conflict that took place between labour/worker with the company at the time of industrial. Analysis of the conflict that occurred between gojek and PT drivers labour Go-Jek, there are three demands of labour/workers against PT Go-Jek, namely tariff refund to the original price, was appointed to the employees, and the transparency of the Fund.